Case Study Handling Approach Using Religious Autistic Children in Pesantren Al-Achsaniyyah in Kudus Regency - Khusna, Istiqomatul; Diana, Diana (BELIA: Early Childhood Education Papers, 2016)
Autistic child is an individual from birth to age 8, children who have autistic disorder have problems in communicating, interacting with the environment, and the attitudes and behavior of the strange and often repeated. In general, these disorders will be visible when the 3-year-old child. For it is very important that autistic disorder is eliminated through therapy, one of the therapies for autistic children that is at institution islamic boarding school Al-Achsaniyyah which is a place-based therapy of religion for children and adults who have special needs such as autistic disorder, cerebral palsy , motor disorders, down syndrome, ADHD and speech delay.This study aims to provide an overview of the therapeutic process and the effectiveness of the therapy given by islamic boarding school Al-Achsaniyyah to children who have autistic disorder. Therapy applied to children, namely occupational, speech, behavior, sensory integration, daily activities, the rhythm of the music, physio therapy, acupuncture and hypno therapy, among these therapies nothing is done every day and on the day only. This study used qualitative research methods case study. Research subjects are children who have autistic disorder aged 6-8 years, while a study conducted at islamic boarding school Al-Achsaniyyah in Kudus. Results of research conducted by the treatment of children with autism using this ABA methods have effectiveness in eliminating the habit of children who do not fit, say something teenagers often activate hand movement without cause. And maintain the results achieved by children and teach children about new things to do, such as children who initially perform bowel and bladder in the pants were taught to do it in the bathroom. The conclusions of this research are children who have received treatment several times from therapists experienced good progress. Suggestions from this study is that in providing therapy, the therapist more patient, as well as the Al-Achsaniyyah institutions to pay more attention to use the facilities and infrastructure therapist.